PENGARUH KOMPETENSI AUDITOR, AUDIT FEE DAN GOOD CORPORATE GOVERNANCE TERHADAP INDEPENDENSI AUDITOR - Onne Arfiangga Djoko Kristianto (Universitas Slamet Riyadi, 2014)
The purpose of this study was to analyze the significance of the influence of the competence of auditors, the audit fee and good corporate governance partially and simultaneously to the independence of the auditor in public accounting firm. To analyze the influence of the dominant variable against the independence of the auditor in public accounting firm. The research method used survey method, the type of data used quantitative and qualitative data. The population in this study is the auditors who work in public accounting firms in the region of Surakarta and Yogyakarta, the sampling technique using quota sampling that a number of 44 respondents, the data collection methods used: questionnaires, observation and documentation. Data analysis techniques used validity, reliability, classic assumption test, multiple linear regression analysis, t test. F test and coefficient of determination. The results were obtained: Competence and significant auditor positive effect on auditor independence in Public Accounting Firm Surakarta and Yogyakarta City. Audit fee and a significant negative effect on the independence of the auditor in public accounting firm. Good corporate governance is positive and significant impact on the independence of the auditor in public accounting firm. Competence of auditors, the audit fee and good corporate governance simultaneously significant effect on the independence of the auditor in public accounting firm. Good corporate governance is the dominant variable influence on the independence of the auditor in public accounting firm. Keywords: Competence of auditors, the audit fee, good corporate governance and independence of auditors